PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI PADA KARYAWAN TRANSMART STAR SQUARE MANADO” - Sajid Arganto; Deetje J. Solang; Stive B. Sengkey (Program Studi Psikologi Universitas Negeri Manado, 2022)
The purpose of this study is to know how influence job satisfaction and organizational commitment of Transmart Star Square Manado employees are. Quantitative research with simple regression analysis with a sample of 47 employees with a total sampling method.). Data collection with questionnaire and questionnaire dissemination techniques. Based on the test results, it can be concluded that H1 was accepted because the job satisfaction variable (x) had a significant influence on organizational commitment (y) judging from the significance value of 0.04 smaller than 0.05 (p < 0.05) and t counted ≥ t table, which is 4,172 ≥ 2,014. the regression coefficient value of the job satisfaction and organizational commitment variables is positively directed which means that when the job satisfaction variable is high, the organizational commitment variable of Transmart Star Square Manado employees will also increase.